Decision support systems: mathematical support : collective monograph - Kashkevich, Svitlana; Stanovska, Iraida; Shknai, Oleh; Lytvynenko, Oleksandr; Artamonov, Yevhen; Veretnov, Andrii; Gaman, Oleksandr; Radchenko, Andrii; Neronov, Serhii; Musaiev, Zaur; Sova, Oleg; Nechyporuk, Olena; et al. (Technology Center PC, 2025)
This collective monograph is the result of the painstaking work of the authors of the study on solving the problems of mathematical support for decision-making using the theory of artificial intelligence. Structurally and logically, the monograph is divided into sections that are structured in a certain thematic area of research on mathematical support using artificial intelligence methods. This work is not comprehensive, and does not claim to be complete in this scientific and theoretical direction. The monograph will be useful for researchers involved in solving problems of mathematical support using the theory of artificial intelligence, the development of new (improving existing) approaches to solving complex technical problems in various fields of human activity. The monograph is also useful for practitioners – designers, developers implementing modern solutions in the field of information technology, engaged in the development of information, information-analytical, and automated systems. Figures 14, Tables 39, References 169 items. This book contains information obtained from authentic and highly regarded sources. Reasonable efforts have been made to publish reliable data and information, but the author and publisher cannot assume responsibility for the validity of all materials or the consequences of their use. The authors and publishers have attempted to trace the copyright holders of all material reproduced in this publication and apologize to copyright holders if permission to publish in this form has not been obtained. If any copyright material has not been acknowledged please write and let us know so we may rectify in any future reprint. The publisher, the authors and the editors are safe to assume that the advice and information in this book are believed to be true and accurate at the date of publication. Neither the publisher nor the authors or the editors give a warranty, express or implied, with respect to the material contained herein or for any errors or omissions that may have been made. Trademark Notice: product or corporate names may be trademarks or registered trademarks, and are used only for identification and explanation without intent to infringe.
Keywords: intelligent systems; decision support systems; artificial intelligence; mathematical support; 004.8; 10.15587/978-617-8360-13-9